Preliminary Exploration of the Similarities and Differences between the Yatga and Guzheng Cultures - Kang, Yijie (International Journal of Social Sciences and Public Administration, 2024)
This study summarizes the origin of the yagta and compares the structural intricacies, tuning systems, and playing techniques of the yagta and the guzheng against diverse cultural backdrops. It illuminates the pivotal role and distinctive significance of the yatga in shaping Mongolian musical traditions. By contextualizing the yatga’s evolution within the historical and cultural milieu of nomadic life and Mongolian ethos, this study enriches our understanding of contemporary guzheng performances and theories. It contributes meaningfully to the vibrant tapestry of zither culture, fostering its broader collision and development.